Slope stability analysis considering the rotated anisotropy in soil properties. Issue 7 (25th January 2021) - Wang, Zhen; Wang, Huanling; Xu, Weiya; Xie, W.C.
Abstract : Purpose: This paper aims to analyze the influence of rotated anisotropy on the stability of slope, the random finite element method is used in this study. Design/methodology/approach: The random field is generated by the discrete cosine transform (DCT) method, which can generate random field with different rotated angles conveniently. Findings: Two idealized slopes are analyzed; it is observed that the rotated angle significantly affects the slope failure risk. The two examples support the conclusion that when the orientation of the layers is nearly perpendicular to the slip surface, the slope is in a relative stable condition. The results of heterogeneous slope with two clay layers demonstrate that the rotated angle of lower layer mainly controls the failure mechanism of the slope, and the rotated angle of upper layer exhibits a significant influence on the probability of slope failure. Originality/value: The method for rotated anisotropy random field generation based on the DCT has a simple expression with few parameters and is convenient for implementation and practical application. The proposed method and the results obtained are useful for analyzing the stability of the heterogeneous slopes in engineering projects.